RFID Demystified: Part 2. Applications within the supply chain. - Wilding, Richard D.; Delgardo, Tiago (The Chartered Institute of Logistics and Transport, 2004)
In our previous article we discussed the technology, benefits and barriers to implementations of Radio Frequency Identification (RFID). In this article we discuss where this technology can be applied. Essentially, it is argued that RFID systems help companies to cut costs, improve customer service, reduce labour, increase accuracy and improve supply chain throughput. RFID systems applications can be used by different industry sectors like the military, retail, industrial, life sciences, logistics, and financial. The military and the life sciences sectors have been the first in using this technology (Das et al, 2002; Harrop et al, 2003; IDTechEx Ltd, 2003a), although within a more expensive and sophisticated context than we may find in most consumer goods supply chains. Surveys of the application of RFID technology find it is being used mostly for industrial/manufacturing - 44.5 percent of the RFID market (Perez, 2003) - and transportation/distribution - 30.3 percent of the RFID market (Perez, 2003).